2014
DOI: 10.1177/2325967114542580
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid Lubricant Properties Are Transiently Deficient After Arthroscopic Articular Cartilage Defect Repair With Platelet-Enriched Fibrin Alone and With Mesenchymal Stem Cells

Abstract: Background Following various types of naturally-occurring traumatic injury to an articular joint, the lubricating ability of synovial fluid is impaired, with a correlated alteration in the concentration and/or structure of lubricant molecules, hyaluronan and proteoglycan-4. However, the effect of arthroscopic cartilage repair surgery on synovial fluid lubricant function and composition is unknown. Hypothesis Arthroscopic treatment of full-thickness chondral defects in horses with (1) platelet-enriched fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…As compared to rodent and rabbit models, synovial fluid acquisition is more reliable in large animal models such as the dog, sheep, and horse, where synovial fluid can be directly aspirated without the requirement for joint lavage. Interestingly, elevated synovial fluid lubricin has been observed in both experimental and naturally occurring PTOA in horses [19][20][21][22]39 , similar to that observed in spontaneous canine RCCL in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As compared to rodent and rabbit models, synovial fluid acquisition is more reliable in large animal models such as the dog, sheep, and horse, where synovial fluid can be directly aspirated without the requirement for joint lavage. Interestingly, elevated synovial fluid lubricin has been observed in both experimental and naturally occurring PTOA in horses [19][20][21][22]39 , similar to that observed in spontaneous canine RCCL in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…However, elevated synovial fluid lubricin concentrations have been reported in humans with tibial plateau fracture and late-stage OA 17,18 . Similar increases in synovial fluid lubricin have also been observed in several studies in both experimentally-induced and naturally occurring PTOA models in horses [19][20][21][22] . However, studies evaluating synovial fluid lubricin in other large animal models, especially large animal models of knee joint instability, are lacking.…”
supporting
confidence: 83%
“…The concentration of HA within each M r range was calculated as the proportion of HA in that range multiplied by the overall HA concentration. Since the molecular weight distribution of HA in SF is typically graded [ 23 ], the exact choice of HA M r bins would not be expected to affect the main results, and we chose the bins used in our previous studies [ 3 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Synovial fluids from animal and human subjects with injured and diseased joints show elevated levels of inflammatory mediators and catabolic factors as well as reduced lubrication and fragmentation of hyaluronic acid compared with healthy controls. 40,41 These changes reflect altered joint biology that can adversely affect stem cell survival and cartilage repair processes. Following arthroscopic treatment of full-thickness chondral defects in horses with APEF, Grissom et al showed a transient reduction in synovial fluid lubrication.…”
Section: Systemic Biologymentioning
confidence: 99%
“…Following arthroscopic treatment of full-thickness chondral defects in horses with APEF, Grissom et al showed a transient reduction in synovial fluid lubrication. 41 In a study of ACL-injured subjects, Cameron et al show variability between individuals with some exhibiting prolonged elevation of inflammatory mediators. 40 Work by Lewis et al showing improved intrinsic cartilage repair in superhealer mice that are able to rapidly dampen the initial inflammatory response after joint injury.…”
Section: Systemic Biologymentioning
confidence: 99%